Core–shell rare-earth-doped nanostructures in biomedicine. Issue 27 (28th June 2018) - Labrador-Páez, Lucía; Ximendes, Erving C.; Rodríguez-Sevilla, Paloma; Ortgies, Dirk H.; Rocha, Ueslen; Jacinto, Carlos; Martín Rodríguez, Emma; Haro-González, Patricia; Jaque, Daniel
Abstract : The current status of the use of core–shell rare-earth-doped nanoparticles in biomedical applications is reviewed highlighting the most relevant advances. Abstract : The current status of the use of core–shell rare-earth-doped nanoparticles in biomedical applications is reviewed in detail. The different core–shell rare-earth-doped nanoparticles developed so far are described and the most relevant examples of their application in imaging, sensing, and therapy are summarized. In addition, the advantages and disadvantages they present are discussed. Finally, a critical opinion of their potential application in real life biomedicine is given.